Disaster Mitigation Management to Reduce Social, Economic, and Health Risks and to Strengthen Community Resilience in Sibalanga Village, North Tapanuli Regency, North Sumatera - Rosalinda Septiani Sitompul; Holmes Rajagukguk; Juandi Nababan; Lambok Simatupang; Dinaria Simamora; Ferdinan Sunarto Silaban; Resipa I. Siburian; Sopar Fidelis Simanullang (Unram Journal of Community Service, 2026)
Sibalanga Village in Adiankoting District, North Tapanuli Regency, was among the areas most severely affected by a series of floods and landslides in late November 2025, which damaged settlements, agricultural land, and basic infrastructure while disrupting local economic activities. Most residents rely on cocoa, petai, and durian as their main commodities; therefore, plantation damage and post-disaster distribution disruptions significantly reduced household income and increased socio-economic and health vulnerabilities. This community engagement program, conducted under the Program Mahasiswa Berdampak, aimed to implement community-based disaster mitigation to reduce social, economic, and health risks while strengthening community resilience. A participatory approach was employed through environmental clean-up activities, tree planting, production of solid organic fertilizer, children’s trauma healing, cocoa processing training under the “TapaRes Kakao (Tapanuli Cocoa Resilience)” initiative, and the provision of appropriate technology tools to local partners, including LDPH and the PKK of Sibalanga Village. The program improved community understanding of flood and landslide mitigation, encouraged small-scale cocoa processing initiatives, strengthened local institutional networks, and fostered social recovery and resilience after the disaster. These findings indicate that integrating disaster mitigation, environmental management, and cocoa-based agro-industry innovation can serve as a model for empowering disaster-prone rural communities while supporting the achievement of SDG 8 and SDG 12.